Coordination Polymers Based on Amphiphilic Oligomeric Silsesquioxanes and Transition Metal Ions (Co2 +, Ni2+): Structure and Stimuli‐Responsive Properties. Issue 5 (23rd April 2021) - Shevchenko, Valery; Bliznyuk, Valery; Gumenna, Mariana; Klimenko, Nina; Stryutsky, Alexandr; Wang, Junlei; Binek, Christian; Chernyakova, Margarita; Belikov, Konstantin
Abstract: Synthesis, structural organization, thermal, and magnetic properties of coordination polymers (OSS‐polymer‐Me) based on amphiphilic oligomeric silsesquioxanes (OSS) and transition metal ions (Co 2+, Ni 2+ ) are reported. The initial amphiphilic OSS containing various ratios of n‐octadecylurethane and carboxyl groups (OSS‐C18 H37 ‐x‐COOH‐y) are characterized with two types of ordered phases. The first one is a supramolecular structure stabilized by hydrogen bonds and characterized with a specific endothermic transition on differential scanning calorimetry thermograms ( T m1 ). The second one is presented by crystalline domains of aliphatic chains with a melting transition peak ( T m2 ). Inclusion of metals has no effect on the magnitude of T m2 while leading to a decrease in the value of the T m1 in comparison to the same compounds without metal. Being located in the nodes of the irregular network structure of OSS‐polymer‐Me, metal ions form ≈2 nm clusters, which connect multifunctional molecules of OSS‐C18 H37 ‐x‐COOH‐y in a supramolecular system similar to disordered metal‐organic framework. The OSS‐polymer‐Me nanocomposites display superparamagnetic properties determined by an adaptive behavior of the intermolecular network. The latter can be modified by the application of an external magnetic field and/or moderate heat. Abstract : Coordination polymers based on Co 2+ or Ni 2+ ions and amphiphilic oligomeric silsesquioxanes containing various ratios of n‐octadecylurethane and carboxyl groups (OSS‐C18 H37 ‐x‐COOH‐y) form a hierarchical stimuli‐responsive supramolecular structure stabilized by a network of intermolecular hydrogen and coordination bonds. The system possesses superparamagnetic properties due to the formation of metal ion nano‐clusters and can be reversibly modified by application of external magnetic field and/or moderate heat.